Unusual Circularly Polarized Photocatalytic Activity in Nanogapped Gold–Silver Chiroplasmonic Nanostructures. (18th August 2015) - Hao, Changlong; Xu, Liguang; Ma, Wei; Wu, Xiaoling; Wang, Libing; Kuang, Hua; Xu, Chuanlai
Abstract : Gold‐gap‐silver nanostructures (GGS NSs) with interior nanobridged gaps are enantioselectively fabricated. Guided byl/d ‐cysteine, the GGS‐L/D (L/D representsl/d ‐cysteine) NSs show reversed plasmon‐induced circular dichroism (CD) signals in the visible region. It is found that the nanogap plays a key role in the plasmonic CD of GGS NSs and the chiroptical response can be tailored by adjusting the amount of cysteine. The anisotropy factor of GGS‐L/D NSs with a 0.5 nm interior gap at 430 nm is as high as ≈0.01. The circularly polarized photocatalytic activity of GGS NSs is examined. It is shown that upon irradiation with left‐circularly polarized light, the catalytic efficiency of GGS‐L NSs is 73‐fold and 17‐fold higher than that of Au nanoparticles (NPs) and Au@Ag core–shell NPs, respectively. Upon irradiation with right‐circularly polarized light, the catalytic activity of GGS‐D NSs is about 71 times and 17 times higher than that of Au NPs and Au@Ag core–shell NPs, respectively. These unique chiral NSs with high plasmonic response can be applied to enantioselective catalysis. Abstract : Guided byl/d ‐cysteine, gold‐gap‐silver nanostructures (GGS NSs) with interior nanogaps, which display exceptionally strong chiroptical activity in the visible light region, are prepared. Based on the fabricated GGS NSs, unexpected circularly polarized photocatalytic activity is discovered under the irradiation with circularly polarized light.